MYB30 and ETHYLENE INSENEITIVE3 antagonistically regulate root hair growth and phosphorus uptake under phosphate deficiency in Arabidopsis. (3rd July 2021) - Xiao, Fei; Zhang, Yiyi; Zhao, Shuangshuang; Zhou, Huapeng
ABSTRACT: Phosphate (Pi) deficiency is one of the major adverse factors limiting plant growth and production. Enhanced RH development is thought to be the typical root morphological response under Pi deficiency, which will enhance the utilization of Pi resources from soil. Here, we report that MYB30-EIN3 module is functionally implicated in Pi deficiency-induced RH development in Arabidopsis. MYB30 and EIN3 antagonistically regulate RH growth via transcriptional regulation of RSL4 as well as other PSR genes, resulting in fine-tuned Pi uptake under Pi deficiency.